Sensitivity of estimators to three levels of correlation between error terms (2010)
A Monte Carlo simulation is employed to investigate the sensitivity of simultaneous equation different levels of correlation between random deviates. Three arbitrary levels of correlation between pairs random deviates were assumed. Three small sample sizes were used in this experiment, N = 15, N=25 and N 40 each replicated 100 times. A number of factors should be taken into account in choosing an method Although system methods are asymptotically most efficient in the absence of violation of independence of random errors, system methods are more sensitive to any kind of error than single equation methods. In practice, models are never perfectly specified nor are they completely free of correlated random deviates. It is a matter of judgment whether the correlation is strong enough to warrant avoidance of system methods. As sample size increases, the TAB for all the estimators decreased consistently except for FIML. OLS, 2SLS, LIML and FIML are remarkably insensitive to the choice of triangular matrices (P1 and P2) when using TAB to judge their performances. Best RSS estimates of 2SLS, LIML, and 3SLS found in the feebly correlated region